KAJIAN KEBIJAKAN PENOLAKAN PARTISIPASI KAUM LAKI-LAKI DALAM PENGGUNAAN ALAT KONTRASEPSI VASEKTOMI DI KELURAHAN SUNGAI ANDAI - Beni Akhmad (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2020)
This study was designed to analyze the rejection of EFA husbands (Fertile Age Couples) using one of the modern contraceptives, namely vasectomy. Using survey research and questionnaires as research instruments, this study qualitatively found that, based on Rogers' innovation adoption theory, modern contraceptives do not have relative advantages, compatibility, trials, complexity, and observational benefits compared to traditional contraception and condoms. The research also found that the main factor in the rejection was the lack of information and knowledge of the husband about the superiority of modern contraceptives. Based on these findings, research recommends increasing information and knowledge about the benefits of modern contraceptives is very important, and community education and education are crucial to increase participation and acceptance of the innovation or program.